Debt Level and the Firm Levered Cost of Capital - De Luca, Pasquale (International Journal of Economics and Financial Issues, 2017)
The cost of capital is one of the most relevant variables in the firm’s valuation models. The well-known models to estimate the cost of capital are based on a defined debt level. Therefore, they can be used only if the debt level is known and constant in the valuation period; consequently, the debt level cannot be defined based on its effects on the cost of capital. The Firm Levered Cost of Capital (FLCC) proposed is a theoretical model structured on the linkage between debt level and the cost of debt through the definition of a non-linear function able to consider debt benefits and costs. Based on FLCC, the firm’s debt level can be defined every time based on its effects on the cost of capital, and then on the firm’s value. In this sense, the FLCC can be considered a theoretical model with a normative function. Keywords: Capital structure, leverage, cost of capital, firm value, discounted cash flow. JEL Classifications: E22, G32